Flow cytometry immune profiling of recurrent and newly diagnosed growth hormone secreting pituitary neuroendocrine tumors: comparison of two clinical cases - Daria Lisina; Valeria Mazeeva; Elena Zakharova; Alyona Sorokina; Lilya Dzhemileva; Andrey Grigoriev; Vilen Azizyan; Alexandra Shutova; Ekaterina Pigarova; Larisa Dzeranova; Galina Melnichenko; Sergei Rumiantsev; et al. (BMC Endocrine Disorders)
Abstract Early detection of aggressive pituitary neuroendocrine tumors (PitNETs) remains challenging due to the absence of reliable markers that can predict disease progression. Aggressive tumors are typically identified through long-term observation. Tumor immune microenvironment (TIME) is crucial for understanding PitNETs' heterogeneity and identifying potential predictors of tumor aggressiveness. In this study, we analyzed immune profile of micro- and macroenvironment in two somatotropinomas (aggressive and non-aggressive) using flow cytometry. We observed lymphopenia and elevated neutrophil levels in the periphery in the patient with tumor recurrence. The aggressive TIME showed greater leukocyte infiltration, with lymphoid cells predominating over myeloid cells along with a higher proportion of CD4 + T cells over CD8 + T cells. We detected double-positive CD4 + CD8 + population, high level of regulatory T cells and a sharp increase in PD-1 + expressing T cells over six months during recurrence. In the blood of the patient with tumor recurrence, we observed reduced granule-mediated cytotoxicity of CD8 + T cells and NK-cells. In the aggressive TIME the number of effector cells producing perforin and granzyme B—both independently and simultaneously was significantly lower. The proportion of CD3-CD20- NK cells and CD3-CD56 + NK cells was low after the first recurrence but increased sharply after six months. The ratio of monocyte subpopulations in tumor differed from that in blood, with CD16 + expressing monocytes predominating in the TIME of both patients. M2 macrophages in TIME rose sharply to 60.8% over six months during recurrence. In several immunological parameters, the patient with tumor recurrence exhibited a more pronounced immunosuppressive profile.